Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Melati Rsj. Prof. Dr. Hb. Saanin Padang - Winda Wulandari; Ramaita .; Dwi Happy Anggita Sari; Vivi Yuderna (CV. ITTC INDONESIA, 2026)
Hallucinations are a sensory perception disorder characterized by the emergence of false sensations, including auditory, visual, olfactory, tactile, and gustatory stimuli that do not actually exist or are unreal. Data from Prof. Hb. Saanin Psychiatric Hospital in Padang indicate that hallucinations have been the most common nursing diagnosis over the past three years (2023–2025). with a total of 17,591 patients. The purpose of this study is to describe the implementation of psychiatric nursing care for Mrs. L with auditory hallucinations in Melati Ward. The method used is a case study with a nursing process approach through five stages: assessment, diagnosis, planning, implementation, and evaluation, conducted over six meetings. The assessment results showed that Mrs. L experienced signs and symptoms of hallucinations, such as hearing whispers and an inability to perform self-care. Case analysis indicates that implementation strategy interventions (SP), such as rebuking hallucinations, medication adherence, engaging in conversations, and scheduled activities, are effective in helping patients control hallucinations. The discussion demonstrates an improvement in the patient’s ability to manage hallucination symptoms and increased independence in self-care. It is expected that the results of this research will increase public understanding of psychiatric nursing care. This understanding will serve as a basis for building awareness, maintaining mental health, and adopting behaviors that support optimal mental well-being.